Ẓawāhir at-Tadākhulāt al-Lugawiyyah: Ta’ṡir al-Lugah al-Jāwiyyah wa as-Sundawiyyah fi al-Lugah al-‘Arabiyyah Ladā Mujtama’ Cirebon Indonesia: ظواهر التداخلات اللغوية: تأثير اللغة الجاوية والسوندوية في اللغة العربية لدى مجتمع شيربون إندونيسيا - Riyadi, Muhsin; Muhammad Amer Mushaf (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2024)
This research aims to explore information related to language interference in Arabic spoken by speakers from the Cirebon community. The ethnic dualism that exists in Cirebon society, namely the Javanese and Sundanese, each of which has its characteristic dialect, is an interesting object in this research. The method used in this qualitative research is observation and in-depth interviews to collect data. The analysis in this research includes three activity streams: data processing and reduction, data triangulation, data presentation, and conclusion. The results of this research show that there is interference between Javanese and Sundanese in Arabic spoken by speakers who are members of the Cirebon community, both in words and sentences. This interference results in several errors in Arabic pronunciation or lahn, whether the errors are visible or vague, some errors change the meaning some do not change the meaning, and some occur repeatedly and non-repeatedly.